2009
DOI: 10.1111/j.1600-0560.2008.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Nephrogenic systemic fibrosis associated with stromal and vascular calcification, report of two cases

Abstract: Nephrogenic systemic fibrosis (NSF) is a systemic fibrosing disorder characterized by the development of large indurated plaques on the skin, primarily in patients with end-stage renal disease (ESRD). Skin biopsy reveals an increased frequency of CD34(+) and Factor XIIa+ cells. Microscopic calcification has been reported in the skin biopsies of rare cases of NSF. The etiology and significance of this calcification is not clear. We present two cases of typical NSF, for which marked stromal and vascular calcific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Renal transplant for patients with NSF does not guarantee disease improvement, but the majority of cases has had successful outcomes, with skin softening and increased joint mobility (94,97,105,106). Treatments with limited benefit include oral corticosteroids, ultraviolet A phototherapy, plasmapheresis, sirolimus, high-dose intravenous Ig, methotrexate, and pentoxifylline (97,100,104,107). Several case reports of extracorporeal photopheresis have shown moderate clinical improvement (100,108,109).…”
Section: Nephrogenic Systemic Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Renal transplant for patients with NSF does not guarantee disease improvement, but the majority of cases has had successful outcomes, with skin softening and increased joint mobility (94,97,105,106). Treatments with limited benefit include oral corticosteroids, ultraviolet A phototherapy, plasmapheresis, sirolimus, high-dose intravenous Ig, methotrexate, and pentoxifylline (97,100,104,107). Several case reports of extracorporeal photopheresis have shown moderate clinical improvement (100,108,109).…”
Section: Nephrogenic Systemic Fibrosismentioning
confidence: 99%
“…Proliferation of dermal spindle cells, increased stromal mucin, and minimal inflammatory infiltrate are common. The epidermis is usually unaffected (98,99), and patients may have abnormal calcification in the dermis and subcutaneous tissue (99,104). The entire dermis may be involved, with the fibrocytes extending through the subcutaneous tissue.…”
Section: Nephrogenic Systemic Fibrosismentioning
confidence: 99%
“…Faktor-XIIIa-positive spindelige und sternförmige Zellen treten ebenfalls auf. Eine mikroskopische Kalzifizierung wurde in Einzelfällen beobachtet [53] . 7 Natriumthiosulfat ist ein Kationenchelator und Antioxidans und bildet hochlösliche Kalziumthiosulfat-Komplexe.…”
Section: Differenzialdiagnosenunclassified
“…Recently, it has been reported that a spectrum of abnormal calcifications, such as dystrophic calcinosis cutis, benign nodular calcifications, metastatic calcinosis cutis, and osseous metaplasia, develop in NSF patients [10][11][12][13][14][15][16][17][18]. Although many NSF patients have been diagnosed, there is no consensus on the etiology or significance of abnormal calcification in NSF.…”
Section: Introductionmentioning
confidence: 99%